ANALISIS HUKUM TERHADAP PENYELESAIAN SENGKETA WANPRESTASI PERJANJIAN GANTI RUGI BERDASARKAN PEMBUKTIAN HUKUM ACARA PERDATA - Sri Wahyuni; Harinanto Sugiono; Asti Wasiska (Program Studi Hukum, Universitas Muhammadiyah Sukabumi, 2026)
Compensation agreements in employment relationships serve as legal instruments that regulate the rights and obligations of employers and employees in the event of losses arising from the performance of work. This study aims to analyze the settlement of breach of contract disputes arising from compensation agreements from the perspective of the law of evidence in Indonesian civil procedural law. This research employs a normative legal research method using statutory, case, and conceptual approaches through an analysis of decision Number 65/Pdt.G/2025/PN Bks. The findings reveal that the settlement of breach of contract disputes is largely determined by the effectiveness of the evidentiary process in civil procedural law. A legally valid compensation agreement constitutes binding evidence of the legal relationship between the parties and may serve as the basis for establishing contractual obligations, proving the occurrence of breach of contract, and demonstrating the resulting losses. The evaluation of documentary evidence, witness testimony, and other admissible evidence forms an essential basis for judicial consideration in resolving disputes. Accordingly, the law of evidence plays a central role in ensuring legal certainty and achieving a fair resolution of breach of contract disputes arising from compensation agreements.